Embedding Communication Skills for Future Financial Planners - L. Celeste Rossetto; Brian Murphy (Australasian Accounting, Business and Finance Journal, 2010)
Financial planners need to have solid knowledge of a range of financial concepts and be adept communicators. Australian universities comprehensively ground students in the necessary content knowledge for their future careers, however, scant attention is paid to the indispensable communication skills that students will need when they enter the professional arena. Students need to accumulate financial planning knowledge but they also have to interact with clients and peers in a business where they will negotiate a professional identity for themselves that will serve their specific expertise. It takes time to develop these skills and to assume a professional identity. The focus of our paper is how to engender this persona at the same time as the students acquire their knowledge. We focus on strategies and activities that were used to embed professional communication skills within a financial planning subject in a regional university through experiential learning and authentic tasks.
Keywords: era2015